They really, really, really don’t like to admit they made mistakes: A critical discourse analysis of appraisal in wrongful convictions - Carmen Ortega-Robles; Encarnación Hidalgo-Tenorio (Language and Cognition)
Besides being unjustly incarcerated, Sabrina Butler, Kristine Bunch, Ru-el Sailor and Larry DeLisle endured various forms of police mistreatment, as detailed in a collection of transcripts from the Wrongful Conviction Podcast (WCP). Understandably enough, their criminalization had a profound impact on their perception of external and internal realities. Given their unique socio-demographic backgrounds, variations in the discursive patterns of their communicative interactions are anticipated. As extensively analyzed in sociolinguistics, both gender and ethnicity influence how individuals construct discourse; particularly, these traits appear to account for how the subjects under study express their emotions and opinions. This is because they are silenced and unable to directly confront their trauma; often, they are incapable of discussing their feelings or identifying those responsible for these traumatic events. Drawing on Appraisal Theory, this paper investigates the language of evaluation used in these texts taken from the WCP. To this end, our analysis of the data is performed using UAM CorpusTool.